Anti-endometriosis Mechanism of Jiawei Foshou San Based on Network Pharmacology - Chen, Yi; Wei, Jiahui; Zhang, Ying; Sun, Wenwei; Li, Zhuoheng; Wang, Qin; Xu, Xiaoyu; Li, Cong; Li, Panhong (Frontiers in Pharmacology, 2018)
Jiawei Foshou San (JFS) is the new formula originated from classic Foshou San formula, composed with ligustrazine, ferulic acid and tetrahydropalmatine. Previously JFS inhibited the growth of endometriosis with unclear mechanism, especially invasion, metastasis and epithelial mesenchymal transition. In this study, network pharmacology was performed to explore potential mechanism of JFS on endometriosis. Through compound-compound target and compound target-disease target networks, candidate targets were analyzed for pathway enrichment. MMP-TIMP was uncovered as one of the core targets. Furthermore, autologous transplantation of endometriosis rat’s model were used to evaluate in vivo effect of JFS on invasion, metastasis and epithelial mesenchymal transition. JFS significantly suppressed the growth, and reduced the volume of ectopic endometrium, with modification of pathologic structure. In-depth study, invasion and metastasis were restrained after treating with JFS through decreasing MMP-2 and MMP-9, increasing TIMP-1. Meanwhile, JFS promoted E-cadherin, and attenuated N-cadherin, Vimentin, Snail, Slug, ZEB1, ZEB2, Twist. In brief, anti-endometriosis effect of JFS might be related to the regulation of epithelial mesenchymal transformation, thereby inhibition of invasion and metastasis. These findings reveal the potential mechanism of JFS on endometriosis and the benefit for further evaluation.